Canton, deuxième agglomération urbaine du monde : un laboratoire pour l’humanité de demain ? - François Moriconi-Ebrard (Confins)
The publication of the first results of the China's population census revealed a growing concentration in the two most populous urban agglomerations on the world : Shanghai has 95 million inhabitants and Guangzhou 70 million. The paper focuses on the second one, whose polycentric urban pattern of “conurbation” evokes the model of the North-Eastern American Megalopolis identified by Jean Gottmann in 1963. According to him, this model prefigured the urban future of humanity, but the demographic density is far much lower than in Canton. Re-examining the great classical models of urban development, the paper raises the question of the exportability of the Chinese way of development to the rest of the world.